Surgical treatment of anomalous origin of the left pulmonary artery from the descending aorta in a teenager: a case report - Guo, Fuzheng; Zhang, Simeng; Du, Zhe; Tai, Jing; Pei, Fengbo; Shi, Yi (Frontiers in Cardiovascular Medicine, 2024)
Anomalous origin of one pulmonary artery (AOPA) is a rare congenital heart disease whose symptoms often occur in infancy, and patients have little chance of surviving into adulthood without timely treatments. AOPA is more frequent in infants and toddlers rather than in adults, and it accounts for only 0.12% of all congenital heart disease cases. In all AOPA cases, the right pulmonary artery from the ascending aorta remains common. This study reported a case with anomalous origin of the left pulmonary artery (AOLPA) from the descending aorta in a teenager who underwent double-incision surgery of median sternotomy and left lateral thoracotomies with favorable outcomes.